2018
DOI: 10.5696/2156-9614-8.17.43
|View full text |Cite
|
Sign up to set email alerts
|

Review of Environmental and Health Impacts of Mining in Ghana

Abstract: Mining has played an important role in the development of Ghana. Like all industries, mining has both benefits and risks for the people living in communities where minerals are found. How these environmental and health impacts are managed by the government, nearby communities and mining companies can either worsen or improve the lives of community inhabitants. The current analysis focuses on the environmental and health impacts of mining in Ghana and blends extant data from the literature as well as the co-aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 19 publications
(25 reference statements)
0
61
0
1
Order By: Relevance
“…Dotson and Hetman (2002) showed that the open pit-mine and quarries exploitation impact has observable impact on the environment land degradation, destruction of vegetation, and the extinction of the native fauna are the most significant signs. Open-pit mines are also a common source of contamination of surface and ground waters [21]. From the sample size of 1204 respondents in Table 1, only 961 respondents equal to (79.82%) indicated that mining affects the surrounding population.…”
Section: Socio-economic Impactmentioning
confidence: 99%
“…Dotson and Hetman (2002) showed that the open pit-mine and quarries exploitation impact has observable impact on the environment land degradation, destruction of vegetation, and the extinction of the native fauna are the most significant signs. Open-pit mines are also a common source of contamination of surface and ground waters [21]. From the sample size of 1204 respondents in Table 1, only 961 respondents equal to (79.82%) indicated that mining affects the surrounding population.…”
Section: Socio-economic Impactmentioning
confidence: 99%
“…The Ghanaian government should pay much attention to agricultural modernisation and education in rural communities. Moreover, it should be stressed that the implementation of mining policies and projects was conducted without paying much attention to local communities and environmental protection [Aboka et al 2018, Siakwah 2017. It may have, in the long-term perspective, a negative impact on environmental conditions and may hamper agricultural sector development.…”
Section: Ghana's Economy and Its Vulnerability To The Dutch Diseasementioning
confidence: 99%
“…Ghana is Africa's second-biggest gold producer and first-largest cocoa producer. Admittedly, the haphazard implementation of mining policies and projects has plunged Ghana into bad environmental conditions [Yeboah 2008, Aboka et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Mining is the extraction of valuable materials and minerals from the earth. Mining practices create a negative environmental impact; therefore, most of the world's nations have passed regulations to decrease the impact of pollution from mines [12][13][14]. Erosion, loss of biodiversity, dust, and contamination of water bodies and soil with HMs and other chemicals are among the environmental issues related to mining activities [15,16].…”
Section: Introductionmentioning
confidence: 99%